2010
DOI: 10.3155/1047-3289.60.9.1026
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel versus Diesel: A Pilot Study Comparing Exhaust Exposures for Employees at a Rural Municipal Facility

Abstract: Many organizations interested in renewable, domestic energy have switched from petroleum diesel to biodiesel blends for use in transportation and heavy-duty equipment. Although considerable evidence exists on the negative health effects of petroleum diesel exhaust exposures in occupational settings, there has been little research examining biodiesel exposures. Working collaboratively with a local municipality, concentrations of particulate matter (PM) and other air toxics were measured at a recycling facility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…There have, however, been three attempts (Table 3) at assessing the health effects of biodiesel exhaust exposure via epidemiology. [70][71][72] The first of these has significant drawbacks and is not published in a peer-reviewed journal. 70 In this study, 763 male road workers had their exposure to rapeseed biodiesel estimated from their job title.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…There have, however, been three attempts (Table 3) at assessing the health effects of biodiesel exhaust exposure via epidemiology. [70][71][72] The first of these has significant drawbacks and is not published in a peer-reviewed journal. 70 In this study, 763 male road workers had their exposure to rapeseed biodiesel estimated from their job title.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…In a more recent study, Traviss et al (2010) measured PM and air toxics (including carbonyls and volatile organics) at a recycling facility in New Hampshire, USA. 72 Heavy machinery at the facility was operated using mineral diesel for 1 day, followed by a blend of 20% soybean biodiesel/80% mineral diesel for 1 day.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown mixed results comparing particulate exposures and DPM across diesel and biodiesel blends, with some finding no difference, (12,17) others showing significant reductions, (13,14,16,(21)(22)(23)(24) and one finding a small increase. (25) Our research revealed increasing tOC and decreasing tEC concentrations associated with B75 use, consistent with previously published studies.…”
Section: Discussionmentioning
confidence: 92%
“…Where safer, less toxic, or non-toxic chemical alternatives can be identified and used in place of environmentally hazardous substances, a reduction in chemical waste and public exposures should follow (LCSP, 2010). A good example of this is the use of biofuels: Traviss et al (2010) reported that employee health risks related to exhaust exposures were much lower when biodiesel blends were used to power heavy-duty equipment, compared with regular petroleum diesel. Industries that adopt cleantech principles may also be able to use existing industrial, commercial or domestic waste as process inputs (e.g., feedstock for bio-energy): this further reduces the public health burden associated with waste management from neighbouring sectors.…”
Section: Direct and Indirect Health Benefitsmentioning
confidence: 99%